Edukacyjne konteksty badań młodzieży - refleksja na temat znaczenia podziałów subdyscyplinarnych (na kanwie doświadczeń współpracy w polskim środowisku socjologicznym) = Educational contexts of youth research - a reflection on the importance of subdisciplinary divisions (on the basis of the experience of cooperation in the Polish sociological community) - Mikiewicz, Piotr (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The text is the author?s reflection on the importance of subdisciplinary divisions in sociology. In particular, the author looks at the motives and functions of distinguishing the research community of sociology of youth and education. The analysis is carried out in two dimensions: meta-scientific and social. As regards the first dimension, the author shows the logic of the formation of sub-disciplinary boundaries as an effort to integrate the research community. The second dimension shows the difficulty of defining a clear demarcation between the sociology of youth and the sociology of education due to the object of interest of these two research communities. The text has an essayistic character and is an expression of the author?s personal reflections and an invitation to a discussion in the discussed problem field.
Keywords: socjologia młodzieży; socjologia edukacji; podziały subdyscyplinarne w socjologii; sociology of youth; sociology of education; subdisciplinary divisions in sociology